Pemodelan Sistem Dinamik dalam Meningkatkan Jumlah Pendaftar di Perguruan Tinggi Swasta XYZ - Silalahi, Fitriani; Manalu, Windy; Silalahi, Fitriani Tupa R. (Universitas Katolik Parahyangan, 2025)
Higher education is an important level of education for society. According to information, private universities (PTS) are the most prevalent in Indonesia. This results in intense competition among PTS, presenting challenges in attracting prospective students, and necessitating effective strategies to reach these students. XYZ University is a campus with advantages such as active learning, reputable faculty, boarding life, comprehensive facilities, and a scenic location. However, the number of applicants to this PTS has fluctuated in recent years. This study aims to develop a dynamic system simulation model to increase the number of applicants. This modeling allows for the analysis of related variables and the side effects of policies. The study's results are expected to provide policy recommendations and strategies to boost the number of applicants. Based on the modeling conducted, four scenarios were tested against the existing simulation data. The simulation results showed that Scenario 2 produced the highest average number of applicants. This scenario involves promotional costs, promotional effectiveness, tuition fees, and reputation in increasing the number of applicants. Policy recommendations to consider include optimizing promotional costs by analyzing and evaluating current promotions, utilizing cost-effective promotions such as social media, and improving webometric rankings in terms of publication and research development to enhance the reputation of the PTS.